Quality of life and compensatory hyperhidrosis following thoracoscopic sympathectomy: a retrospective cohort study - Jingsi Wang; Shengliang Zhao; Bo Tang; Mingzhang Xiang; Jigang Dai; Quanxing Liu (Journal of Cardiothoracic Surgery)
Abstract Background Palmar hyperhidrosis (PH), characterized by excessive palm sweating, significantly impacts quality of life (QOL) in affected individuals, particularly young adults. This study aimed to evaluate the efficacy of video-assisted thoracoscopic sympathectomy (VATS) in improving symptoms and QOL among 816 patients with PH. Methods This retrospective study included 816 patients with PH, all of whom underwent VATS under general anaesthesia. One-year follow-up via phone surveys was used to assess symptom changes and side effects. Paired t tests were used to compare pre- and postoperative QOL scores, and linear regression was used to analyse the effects of various factors on QOL changes. Results The cohort consisted of 359 males and 457 females, with a mean age of 24.98 ± 6.47 years. All patients underwent VATS, with a 91% success rate, and the mean operative time was 53.2 ± 24.7 min. Postoperative complications included 43 cases of incision infections, 194 cases of chest pain, and 82 cases of pneumothorax; compensatory hyperhidrosis (CH) occurred in 53.80% of the T3 group and 43.74% of the T4 group after one month, with significant differences noted at the 24-month follow-up. Furthermore, the QOL scores significantly improved from 38.25 ± 3.61 preoperatively to 69.07 ± 3.48 at one year postoperatively (P < 0.05). Conclusions VATS offers a reliable and effective treatment for severe PH, significantly enhancing patients’ overall QOL. Future research should focus on long-term outcomes and the applicability of this treatment across diverse populations to further advance the clinical management of PH.